The plot chickens - Auch, Mary Jane.; Auch, Herm. (New York : Holiday House, 2009)
Henrietta the chicken loves to read so much that she decides to write a book herself, but she has trouble finding someone to publish a book written by a chicken, and then, when she publishes it herself and it gets a terrible review in "The Corn Book," Henrietta is devastated.
Wilson's Children, July 2009.
School Library Journal, March 2009.
Book Links (A.L.A.), January 2010.
Horn Book, October 2009.
Wilson's Children.
School Library Journal.
Keywords: Chickens -- Juvenile fiction; Authorship -- Juvenile fiction; Chickens -- Fiction; Authorship -- Fiction; Humorous stories; Chickens -- Fiction; Authors -- Fiction; Humorous fiction; Humorous fiction; Picture books for children